Development the method of organizing a secure data channel in the water supply monitoring system - Сидоренко, Володимир Володимирович; Буравченко, Костянтин Олегович (Technology audit and production reserves, 2016)
This article describes a method of securing data in water supply monitoring system. The main aim of the study is to information security that is transmitted in the system of monitoring of water supply process through wireless networks. It is necessary to find a system architecture that will provide stability to the interception of information. In this paper we propose to use the encryption algorithm based on an asymmetric public key to create a secure TCP-session between the client (data acquisition points) and the server. This method allows creating a secure data transmission channel on the Internet using only one static IP-address from the data acquisition server. Studies indicate that this method has advantages over the use of the existing operating system in the data acquisition device. The author proposes to use this method of constructing the water supply monitoring system for data exchange between the data acquisition points and the server. The research results can be used by designers of water supply systems, automation and remote control, engaged in the field of water supply.